Fauna Austriaca. Die Fliegen (Diptera), nach der analytischen Methode bearbeitet - Schiner, J. R. (Zweiter Theil. Vienna, 1864)
In the second part of his great work on the Diptera of Austria, published in 1864, Schiner commences with his second great section of the family Muscidae, continues through the Phoridoe, of which he makes a distinct family, to the numerous families of the great group Nematocera, Latr., and concludes the order with the Pupiparous families Hippoboscidoe and Nycteribidoe, which are thus placed at rather too great a distance from their unquestionable allies, the Muscidoe and OEstridoe. The whole of the European genera are characterized, as are all the species occurring in Germany, and under each genus is given a list of the European species not found in Germany. The whole work is arranged as a dichotomous table, with the detailed generic and specific descriptions interwoven, in the same manner as in Redtenbacher’s well-known work on the Austrian Beetles; and there is also, at the commencement, a tabular synopsis of families, subfamilies, and genera, to facilitate reference to the body of the work. By these means the inconvenience experienced in consulting many treatises tabularly arranged is entirely removed. The species of Diptera described in this volume are arranged in the following families:[long dash]Muscidoe Acalypteroe, including 156 genera; Phoridoe, with four genera ; Bibionidoe, with seven genera; Simulidoe, with the single genus Simulia ; Cecidomyidoe, with fifteen genera; Mycetophilidoe, with forty-five genera; Rhyphidoe, with the single genus Rhyphus ; Tipulidoe, with thirty-nine genera; Chironomidoe, with seven genera; Culicidoe, with five genera; Psychodidoe, with six genera; Hippoboscidoe, with eight genera; and Nycteribidoe, for Nycteribia alone. The genera Blepharicera (Macq.), Macropeza (Meig.), Spodius (Loew), Pachyneura (Zett.), Corynocera (Zett.), Dixa (Meig.), and Orphnephila (Hal.) are placed as "genera incertoe sedis" at the end of the Nematocerous families (pp. 637-643). The total number of Austrian species (including those of the last-mentioned genera) is over 1380, 628 (or nearly half) belonging to the second division of the Muscidae.